THE EFFECTIVENESS OF LEMON JUICE (Citrus limon) TOWARD PYRAMIDAL NEURON CELLS OF MALE WHITE MICE’SCEREBRAL CORTEX THAT EXPOSED BY MONOSODIUM GLUTAMATE (MSG) - Pepi Arifiyani; Hikmah Fitriani; Rachmanda Haryo Wibisono (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: The consumption rate of Monosodium Glutamate (MSG) in Indonesia remains high. Lemon is an antioxidant and neutralizer of free radicals which contains vitamin C and phytochemicals to prevent the long-term effects of MSG to pyramida cells. This study aims to test the effect of oral administration of lemon juice (Citrus limon) to the number of pyramidal neuron cells. Methodology: This experimental study employed 30 male white mice aged 2.5 to 3 months. Those mice were randomly divided into five control-groups: Normal Control (KN), Negative Control (K-) was treated with 4 mg/grBB MSG, Dose Group 1 (KD1) was treated with 3.33 ml/kgBB lemon juice, Dose Group 2 (KD2) was treated with 6.67 ml/kgBB lemon juice, and Dose Group 3 (KD3) was treated with 13.33 ml/kgBB lemon juice. Kruskal Wallis test was used to determine the difference in distribution between groups, followed with Post hoc Mann Whitney test. Results: After 28 days of treatment, the average number of pyramidal neuron cells in dose group 1 (637 cells) was higher than in negative control (589.5 cells) (p=0.078). The average number of pyramidal neuron cells in dose group 3 (482,5 cells) was lower than in the negative control (589.5 cells) (p=0.016). The statistical result shown that there were groups with a significant difference in pyramidal cells number. Mann-Whitney analysis of pyramidal cells number had shown that there was a significant differencebetween group KD3 and KD1, KD3 and K (-), KD3 and KD2. Conclusion: Lemon juice (Citrus limon) in precise dose has a beneficial effect to reduce the excitotoxic effect of MSG. Further studies is needed to validate the active compound and toxicity effect of lemon juice. Keywords: Pyramidal neuron cells, monosodium glutamate, lemon (Citrus limon)